Study by Optical Spectroscopy of Bismuth Emission in a Nanosecond-Pulsed Discharge Created in Liquid Nitrogen - Anna V. Nominé; Cédric Noel; Thomas Gries; Alexandre Nominé; Valentin A. Milichko; Thierry Belmonte (Molecules, 2021)
Time-resolved optical emission spectroscopy of nanosecond-pulsed discharges ignited in liquid nitrogen between two bismuth electrodes is used to determine the main discharge parameters (electron temperature, electron density and optical thickness). Nineteen lines belonging to the Bi I system and seven to the Bi II system could be recorded by directly plunging the optical fibre into the liquid in close vicinity to the discharge. The lack of data for the Stark parameters to evaluate the broadening of the Bi I lines was solved by taking advantage of the time-resolved information supported by each line to determine them. The electron density was found to decrease exponentially from 6.5 ± 1.5 × 1016 cm−3 200 ns after ignition to 1.0 ± 0.5 × 1016 cm−3 after 1050 ns. The electron temperature was found to be 0.35 eV, close to the value given by Saha’s equation.